Effects of progressive muscle relaxation technique on affective and somatic signs in nursing students taking objective structured clinical examination - Nurvita Risdiana; Jefry Leo Sandy; Johan Johan (Faculty of Medicine, Universitas Islam Indonesia, 2021)
Background: Objective Structured Clinical Examination (OSCE) is an instrument for an evaluation test to asses observable skills. However, this situation of the test can lead to anxiety for students expressed in affective and somatic signs. Progressive muscle relaxation technique is one of non-pharmacology therapies and can be used to decrease the affective and somatic signs in the students. Objective: This study aims to determine effects of the progressive muscle relaxation technique on affective and somatic signs in nursing students when taking the OSCE. Methods: This study was a quasi-experimental with a pre-test and post- group design. Fifty eight participants were selected by inclusion criteria and divided into two groups (a treatment group and a control group). The progressive muscle relaxation before the OSCE was conducted for 30 minutes. Zung’s self-rating anxiety (ZSAS) was applied to measure the affective signs. A sphygmomanometer, manual heart rate palpation, and thorax inspection were used to measure the somatic signs. The data were analysed by using a Wilcoxon test.Results: The Wilcoxon test showed that the effects of progressive muscle relaxation technique on the affective signs indicated p-value of 0.0001 (p<0.005). Then it also affected the somatic signs as occurred in systolic blood pressure with p-value of 0.00, diastolic blood pressure with p-value of 0.004, heart rate with p-value of 0.00, and respiration rate with p-value of 0.00. The affective and somatic signs in the treatment group decreased after the treatment was given. However, they were not found in the control group.Conclusion: There are effects of progressive muscle relaxation technique on affective and somatic signs in nursing students when taking the OSCE. The affective and somatic signs in the treatment group were lower than in the control group.